Faktor-Faktor Eksternal Yang Berhubungan dengan Sisa Makanan Biasa Pasien Bangsal Rawat Inap RSUD Salatiga - Murjiwani, Endah, Endang Nur Widyaningsih, S.ST.,M.Si,Med, Farida Nur Isnaeni, S.Gz., M.Sc Dietisien (2013)
Background: Nutritional service activities have the aim to provide quality food and quantity of nutrients as needed. Terms of goos quality of food if the food has high taste, appearance, interesting presentation, thus encouraging patients spend on food. Reduced of food scraps was caused by variations in taste (flavor, temperature, smell, texture), and variations in appearance (color, large portions, shape, manner of presentation). Purpose: To know external factors associated with usuals food scraps in inpatients ward at general hospital area of salatiga Method of the Research: The research implemented a survey-observational with cross-sectional approach. Subject of the research is 33 individuals selected by using propotional random sampling. Data of intake protein, vitamin C, and drinking habits of tea was taken by recall procedures with 3x24 hour by random day and data of hemoglobin concentration by hemoque methode. Data is analyzed by using correlation test of Pearson-product moment. Result: Based on univariate analysis, most levels of protein intake are included in the category of research subjects less as many as 81.8%, most of the intake levels of vitamin C research subjects included in the category of less as many as 63.6%, research subjects with daily consumption of tea as much as 60.6%. The results of hemoglobin levels 36.4% of normal subjects, whereas hemoglobin levels are not normally subject to 63.6%. The results of Pearson product moment correlation test p value = 0.870, p=0,198, p=0,455 Conclusion: It can be concluded that there is no correlation between intake protein, vitamin C, and drinking habits of tea with hemoglobin levels in females student at state 1 high school of Mojolaban Sukoharjo regency.